The Impact of Fiscal Policy to the Economy Growth of Lao PDR - PHIMPHISANE, VIENGKHONE; VONGPADITH, Vongphachanh; SENGDALA, Chansamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objectives of this study were to 1) Identify the impact of government revenue and government expenditure on the economic growth of Lao PDR; and 2) Analyze how tax revenue, non-tax revenue, grants, recurrent expenditure and public investment expenditure impacted on economic growth. The study used time series data from 2001 to 2024. To learn more, we were given access to secondary data from the Bank of the Lao PDR and World Bank. The analyses for this data were performed using the Ordinary Least Squares (OLS) model. The results in clouded that: 1) the government revenue and government expenditure did not have a statistically significant effect on economic growth. The model as a whole was not statistically significant indicating that these variables alone could not adequately explain changes in GDP growth. 2) Tax revenue and public investment expenditure have positive and statistically significant effects on GDP growth. This implies that improvements in tax collection efficiency and increased public investment, particularly in infrastructure development, can contribute positively to economic expansion in Lao PDR. In contrast, recurrent expenditure was found to have a negative and statistically significant effect on economic growth, suggesting that excessive administrative spending may reduce economic efficiency and limit long-term growth potential. Meanwhile, non-tax revenue and foreign grants were not found to have statistically significant impacts on economic growth.